Canopy recovery after drought dieback in holm-oak Mediterranean forests of Catalonia (NE Spain) - Lloret, Francisco; Siscart, Daniel; Dalmases, Carles (Global Change Biology, 2004)
Climate change is likely to produce more frequent and longer droughts in the Mediterranean region, like that of 1994, which produced important changes in the Quercus ilex forests, with up to 76% of the trees showing complete canopy dieback. At the landscape level, a mosaic of responses to the drought was observed, linked to the distribution of lithological substrates. Damage to the dominant tree species (Q. ilex) and the most common understorey shrub (Erica arborea) was more noticeable on the compact substrates (breccia) than on the fissured ones (schist). This result was consistent with observations documenting deeper root penetration in schist than in breccia materials, allowing the plants growing on fissured substrates to use water from deeper soil levels. Smaller plants were more vulnerable to drought than larger plants in the trees, but not in the shrubs. Overall, Q. ilex was more affected than E. arborea. The resilience of the system was evaluated from the canopy recovery 1 year after the episode. Stump and crown resprouting was fairly extensive, but the damage pattern in relation to substrate, plant size, and species remained similar. The effect of recurrent drought episodes was studied on vegetation patches of Q. ilex located on mountain slopes and surrounded by bare rock. We observed that plants that resprouted weakly after a previous drought in 1985 were more likely to die or to produce poor regeneration in 1995 than plants that had resprouted vigorously. Vegetation patches located on the lower part of the slope were also less damaged than patches situated uphill. The study provides evidence of relevant changes in forest canopy as a consequence of extreme climate events. The distribution of this effect across the landscape is mediated by lithological substrate, causing patchy patterns. The results also support the hypothesis that recurrent droughts can produce a progressive loss of resilience, by depleting the ability of surviving plants to regenerate.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: climate change; Erica arborea; Quercus ilex; resilience; resprouting; severity; shift; threshold